Contribution of an instructional module for lymph node evaluation: An experiment - Francine Lima Fulquini; Cristina Mara Zamarioli; Bárbara Gadioli; Luciana Kusumota; Fernanda Raphael Escobar Gimenes; Emília Campos de Carvalho (Universidade de São Paulo, 2021)
Objective: to evaluate the contribution of an instructional module identifying the number and characteristics of lymph nodes by undergraduate nursing students. Method: an experimental, randomized, controlled and masked study using an instructional module for intervention. The 68 students who made up the control group or the experimental group performed the prototype lymph node palpation in the initial and final phases, following the free registration of the characteristics and number of these structures. Between the phases, the instructional module (palpation prototype and a registration guide instrument) was applied to the experimental group. Descriptive statistics and mixed linear regression were used for analysis. Results: the experimental group showed greater accuracy (p<0.05) in the evaluation of the size, consistency, mobility and coalescence of the lymph nodes in the final phase when compared to the control; it also showed more chances to correctly evaluate the consistency ( OR 45,26; 95% CI<7,74>‡<264.54> p<0.0001), mobility (OR 55.95; CI 95% 12.45 - 251.60; p<0.0001) and size (OR 25.64; CI 95% 3.92 - 160.2; p=0.0002) of the lymph nodes. Conclusion: the results reinforce the contribution of the instructional module to increase the knowledge of nursing students about the evaluation of lymph nodes.